The effect of major salivary glands hypertrophy on rat’s spermatogenic epithelium ultrastructure - V. V. Ivanova; D. I. Тikhonov; I. V. Mil’to; O. N. Serebrjakova; E. A. Gereng; R. I. Pleshko (Бюллетень сибирской медицины)
Purpose. The aim of this study was to ascertain the characteristics of major salivary glands endocrine effect onspermatogenesis.Materials and methods. Mature white outbred male rats (2 months, 153 ± 18 g) consisted of the following groups (each containing 30 rats): intact, control, and group of rats subjected to multiple amputation of incisors. To achieve hypertrophy of major salivary glands multiple amputation of incisors was performed: incisors were cut to a level of 1-2 mm above the gingival margin under ether anesthesia once every 3 days within 2 weeks. Animals of the control group were anesthetized with ether at the same time. Rats were sacrificed by CO2 asphyxia after 2, 3, 4, 6, 8 and 10 weeks after the first amputation of incisors. Fragments of the rat testes were examined on a JEM-1400 “JEOL” (Japan) transmission electron microscope. On electron microscopy images the specific vacuolization of the cytoplasm of Sertoli cells, spermatogonia, spermatocytes and spermatids (standard units) was analyzed by the point counting method. In spermatogenic cells the proportion of mitochondria (%) with morphological signs of swelling was assessed.Results. Transient ultrastructural changes of Sertoli and spermatogenic cells develop in the rats convoluted seminiferous tubules as a result of multiple amputation of the incisors, such as phagosomes and pronounced vacuolization in the Sertoli cells cytoplasm, cytoplasm vacuolization and mitochondrial swelling in spermatogenic cells. Sporadic spermatogenic cells with signs of nuclear (chromatin fragmentation, its condensation on the periphery of the nucleus) and cytoplasm (destruction of membrane organelles) destruction appeared as a result of multiple incisors’ amputation. Ultrastructural changes of Sertoli and spermatogenic cells are most pronounced at 2-3 weeks, decrease at 4 week and are completely leveled by the 6th week of the experiment.Conclusion. Hypertrophy of major salivary glands, caused by multiple amputations of incisors, has similar to sialoadenectomy effect on the spermatogenic epithelium. Multiple incisors’ amputation cause transient  depression of granular convoluted cells function. Probably submandibular gland granular convoluted tubules cells endocrine factors make the greatest contribution to the regulation of spermatogenesis in rats.